2018
DOI: 10.1352/1934-9556-56.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Life Outcomes and Higher Education: The Need for Longitudinal Research Using a Broad Range of Quality of Life Indicators

Abstract: Higher education is increasingly becoming an option for young adults with intellectual disability (ID). Although initial evaluations of postsecondary education for this population have been promising, a broader "quality of life" framework needs to be adopted in order to truly understand the impact of these programs. Moreover, researchers and program evaluators must collect longitudinal data that follows former students for multiple years and uses multiple measures. We conducted a pilot evaluation of the life o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Higher education institutions offer social opportunities that can lead to increased social networks and friendships (Alqazlan et al, 2019; May, 2012; O'Connor et al, 2019; Sheppard‐Jones et al, 2018). Consistent with previous research (Gibson, 1997; Lobban, 2002; May, 2012; Rillotta, Arthur, et al, 2020; Rillotta, Gobec, et al, 2020; Sheppard‐Jones et al, 2018), participation in the UTHP provided participants the opportunity to interact with various individuals. However, results suggested that natural connections, beyond the formal roles of mentors and university staff, were not occurring or were not sustained over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher education institutions offer social opportunities that can lead to increased social networks and friendships (Alqazlan et al, 2019; May, 2012; O'Connor et al, 2019; Sheppard‐Jones et al, 2018). Consistent with previous research (Gibson, 1997; Lobban, 2002; May, 2012; Rillotta, Arthur, et al, 2020; Rillotta, Gobec, et al, 2020; Sheppard‐Jones et al, 2018), participation in the UTHP provided participants the opportunity to interact with various individuals. However, results suggested that natural connections, beyond the formal roles of mentors and university staff, were not occurring or were not sustained over time.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting social inclusion in university settings can involve pairing participants with peer mentors who can encourage and facilitate connections (Hafner et al, 2011; Rillotta, Arthur, et al, 2020; Rillotta, Gobec, et al, (In Press) 2020; Sheppard‐Jones et al, 2018), a strategy utilised in higher education for students with and without disabilities (Björnsdóttir, 2017; Colvin & Ashman, 2010). In the current study, mentors were highly valued by participants, with many having a continued role in their lives post‐program.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies reported descriptions of a total of 22 PSE-IDDs. All these studies but two focused on a single PSE-IDD; Carter et al (2019) and Sheppard- Jones et al (2018) each included five PSE-IDDs. Seven studies did not provide program descriptions; three of these studies included multiple PSE-IDDs (Mock & Love, 2012;Moore & Schelling, 2015;Plotner & Marshall, 2015), and four studies did not provide any descriptions of the PSE-IDDs.…”
Section: Pse-idd Program Descriptionsmentioning
confidence: 99%
“…In another study, 67% of peer mentors reported greater social opportunities for students with IDD after one academic year (S. M. Ryan, 2014). In addition, 94.4% of PSE-IDD graduates reported that they could go on a date compared with 39.3% of the National Core Indicators sample (i.e., a sample of adults with IDD receiving disability-related funding from their state; Sheppard- Jones et al, 2018).…”
Section: Table 1 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation